GrainGenes: centralized small grain resources and digital platform for geneticists and breeders. (18th June 2019) - Blake, Victoria C; Woodhouse, Margaret R; Lazo, Gerard R; Odell, Sarah G; Wight, Charlene P; Tinker, Nicholas A; Wang, Yi; Gu, Yong Q; Birkett, Clay L; Jannink, Jean-Luc; Matthews, Dave E; Hane, David L; et al.
Abstract: GrainGenes (https://wheat.pw.usda.gov or https://graingenes.org ) is an international centralized repository for curated, peer-reviewed datasets useful to researchers working on wheat, barley, rye and oat. GrainGenes manages genomic, genetic, germplasm and phenotypic datasets through a dynamically generated web interface for facilitated data discovery. Since 1992, GrainGenes has served geneticists and breeders in both the public and private sectors on six continents. Recently, several new datasets were curated into the database along with new tools for analysis. The GrainGenes homepage was enhanced by making it more visually intuitive and by adding links to commonly used pages. Several genome assemblies and genomic tracks are displayed through the genome browsers at GrainGenes, including the Triticum aestivum (bread wheat) cv. 'Chinese Spring' IWGSC RefSeq v1.0 genome assembly, the Aegilops tauschii (D genome progenitor) Aet v4.0 genome assembly, the Triticum turgidum ssp. dicoccoides (wild emmer wheat) cv. 'Zavitan' WEWSeq v.1.0 genome assembly, a T. aestivum (bread wheat) pangenome, the Hordeum vulgare (barley) cv. 'Morex' IBSC genome assembly, the Secale cereale (rye) select 'Lo7' assembly, a partial hexaploid Avena sativa (oat) assembly and the Triticum durum cv. 'Svevo' (durum wheat) RefSeq Release 1.0 assembly. New genetic maps and markers were added and can be displayed through CMAP. Quantitative trait loci, genetic maps and genes from the Wheat Gene Catalogue are indexed and linked through the Wheat Information System (WheatIS) portal. Training videos were created to help users query and reach the data they need. GSP (Genome Specific Primers) and PIECE2 (Plant Intron Exon Comparison and Evolution) tools were implemented and are available to use. As more small grains reference sequences become available, GrainGenes will play an increasingly vital role in helping researchers improve crops.